Laboratory characteristics of blastocystis invasion in patients with chronic viral hepatitis - A. S. Sigidaev; V. S. Sukachev; M. V. Kurtukov; K. V. Zhdanov; S. S. Kozlov; K. V. Kozlov; A. V. Laskin; E. A. Tarasova; M. A. Suvorova (Журнал инфектологии, 2014)
Based on the survey results in 1322 patients found that patients with hronic viral hepatitis (CVH) blastocysts are found more often than in the group of individuals without concomitant pathology of the hepatic-biliary system (28.8% vs. 5.5%, respectively). In healthy individuals the blastocyst revealed more often in the summer, peaking in July and August, while in patients with CVH Blastocystis most frequently observed in winter. The high incidence of Blastocystis sp. CVH patients suggests that the pathology of the hepatic-biliary system fosters a supportive environment in the gastrointestinal tract for the colonization of its blastocyst. Molecular biological methods of investigation revealed that the subtype antroponozny blastocysts met in this population, 5.3 times less likely than those without concomitant liver disease.